The Effect of Quality Assessment and Directional Goal Commitment on Auditors' Acceptance of Client-Preferred Accounting Methods - Kadous, Kathryn; Kennedy, S. Jane; Peecher, Mark E. (The Accounting Review, 2003)
Previous research demonstrates that auditors' directional goals influence their reporting decisions. For example, when auditors have goals of accepting client-preferred accounting methods, they tend to exploit ambiguity in reporting standards to justify those methods, even when they are aggressive (Hackenbrack and Nelson 1996). We report an experimental investigation of the likely effectiveness of regulation designed to curb this tendency. Specifically, regulators suggest that having auditors identify benchmarks or assess the quality of various methods will “raise the bar” for method acceptability, thereby reducing auditor acceptance of aggressive reporting methods. However, this reasoning ignores the fact that ambiguity typically surrounds quality assessment. Following motivated reasoning theory, we argue that, in order to meet the increased standard for acceptability, auditors with high commitment to directional goals will exploit the ambiguity surrounding the quality of various methods when making quality assessments, with the result that the client-preferred method will be deemed best, or at least of high enough relative quality to be used. This theory suggests that auditor acceptance will increase with goal commitment, and that the increase will be most dramatic when quality assessment is performed. Results of our experiment support our hypotheses that performing a quality assessment amplifies the effects of auditors' directional goals on their acceptance of client-preferred methods and on their ratings of the quality of that method. Moreover, auditors making quality assessments are more likely to identify the client's method as the most appropriate method when they are more committed to their directional goals. An implication of our theory and results is that regulation (such as SAS No. 90) that requires auditors to make quality assessments may decrease auditors' objectivity when auditors have directional goals to accept client methods.